Influence : the psychology of persuasion / Robert B. Cialdini - Cialdini, Robert B.
In this highly acclaimed New York Times bestseller, Dr. Robert B. Cialdini-the seminal expert in the field of influence and persuasion-explains the psychology of why people say yes and how to apply these principles ethically in business and everyday situations